The cost-effectiveness of total laparoscopic hysterectomy compared to total abdominal hysterectomy for the treatment of early stage endometrial cancer. Issue 4 (18th April 2013) - Graves, Nicholas; Janda, Monika; Merollini, Katharina; Gebski, Val; Obermair, Andreas; ,
Abstract : Objective: To summarise how costs and health benefits will change with the adoption of total laparoscopic hysterectomy compared to total abdominal hysterectomy for the treatment of early stage endometrial cancer. Design: Cost-effectiveness modelling using the information from a randomised controlled trial. Participants: Two hypothetical modelled cohorts of 1000 individuals undergoing total laparoscopic hysterectomy and total abdominal hysterectomy. Outcome measures: Surgery costs; hospital bed days used; total healthcare costs; quality-adjusted life years; and net monetary benefits. Results: For 1000 individuals receiving total laparoscopic hysterectomy surgery, the costs were 509 575 higher, 3548 hospital fewer bed days were used and total health services costs were reduced by 3 746 221. There were 39.13 more quality-adjusted life years for a 5 year period following surgery. Conclusions: The adoption of total laparoscopic hysterectomy is almost certainly a good decision for health services policy makers. There is 100% probability that it will be cost saving to health services, a 86.8% probability that it will increase health benefits and a 99.5% chance that it returns net monetary benefits greater than zero.